PRÁTICAS PEDAGÓGICAS NA EDUCAÇÃO INFANTIL - Fernando Wolff Mendonça; Diogo Almeida e Silva (Edufatecie, 2020)
It is difficult to define music and its entire universe in a few words or in just one conception, considering its innumerable relationships with human beings. Thinking of contributing to the improvement of educational work in early childhood education, we propose to study pedagogical practices through music. Since children are being inserted into the school environment from the age of 4 months on, the responsibility for child development is now shared between the family and the school institution. In this sense, the Law of Directives and Basis for National Education -LDBEN -of nº 9.394 / 1996 and national documents, emphasize the importance of pedagogical work that promotes the integral development of the child who is in the nursery or preschool. Given this context, this work aims to discuss the contributions of pedagogical practices in early childhood education, addressing music as a language, for the development of higher psychological functions, that is, thehuman skills of children. This is a bibliographic research that makes a historical review about music and its relationship with man and with the society in which it is inserted. We are based on the framework of Cultural Historical Theory, proposing a reflection on pedagogical practices that explore the musical universe, to provide opportunities for different forms of the humanization process in new generations.